Inverse relationship between body mass index and mortality in older nursing home residents: a meta‐analysis of 19, 538 elderly subjects. Issue 11 (7th August 2015) - Veronese, N.; Cereda, E.; Solmi, M.; Fowler, S. A.; Manzato, E.; Maggi, S.; Manu, P.; Abe, E.; Hayashi, K.; Allard, J. P.; Arendt, B. M.; Beck, A.; et al.
Summary Body mass index (BMI) and mortality in old adults from the general population have been related in a U‐shaped or J‐shaped curve. However, limited information is available for elderly nursing home populations, particularly about specific cause of death. A systematic PubMed/EMBASE/CINAHL/SCOPUS search until 31 May 2014 without language restrictions was conducted. As no published study reported mortality in standard BMI groups (<18.5, 18.5–24.9, 25–29.9, ≥30 kg/m2), the most adjusted hazard ratios (HRs) according to a pre‐defined list of covariates were obtained from authors and pooled by random‐effect model across each BMI category. Out of 342 hits, 20 studies including 19, 538 older nursing home residents with 5, 223 deaths during a median of 2 years of follow‐up were meta‐analysed. Compared with normal weight, all‐cause mortality HRs were 1.41 (95% CI = 1.26–1.58) for underweight, 0.85 (95% CI = 0.73–0.99) for overweight and 0.74 (95% CI = 0.57–0.96) for obesity. Underweight was a risk factor for higher mortality caused by infections (HR = 1.65 [95% CI = 1.13–2.40]). RR results corroborated primary HR results, with additionally lower infection‐related mortality in overweight and obese than in normal‐weight individuals. Like in the general population, underweight is a risk factor for mortality in old nursing home residents. However, uniquely, not only overweight but also obesity is protective, which has relevant nutritional goal implications in this population/setting.